How social media influences the self-image and body image among female and male adolescents - Merete Kolberg Tennfjord; Ashley Rebecca Bell; Ragnhild Eg (PLoS ONE, 2025)
Parents, peers, and social media are the primary drivers of sociocultural influence among young people, where social media is considered the most pervasive and persuasive of these drivers. However, there is a need for a more nuanced understanding of this influence, considering the differences in how young males and females view their self-images and body images. This study combined qualitative data from focus-group interviews and a national survey to investigate social media influences on Norwegian adolescents’ body image and self-image. Forty-eight adolescents (58% females) attending secondary schools mean age 15.9 (age range 15–19 years) participated in eight focus-group interviews. Their responses to the questions about social media’s influence on body image were analyzed thematically. The focus group interviews were succeeded six months later by a national survey administered to adolescents (59% females) attending secondary schools with a mean age of 18 (age range 16–20 years). One-hundred-twenty-four responses to social media’s impact on their self-images were analyzed both quantitatively and qualitatively. Triangulating the data suggested a tendency for social media to have a negative impact on adolescents’ body image and self-image. Females, more than males, viewed social media’s impact on their self-image as negative, and most of these negative descriptions were related to unattainable ideals and idealized body representations. A deeper insight into the male’s experiences through focus groups revealed that males do experience body-image pressure but that it is rarely talked about. Further, from both datasets adolescents take measures to pursue social media for its positive content, whereas, from the interviews, young males used body-related content on social media as motivation to work towards building their ideal masculine body. Body positivity was talked about in the interviews, where females viewed this as positive, whereas males could not relate to this trend. These findings highlight the need for novel strategies to shift focus away from appearance-related self-images and reduce body-image pressure on social media.